The Influence of Human Rights on International Law
XI, 248 p.
Keywords: This volume discusses the impact of human rights law on other fields of international law. Does international human rights law modify other fields of international law? Contributions focus on possible spillover effects of human rights on international economic or international criminal law. Does international human rights law have a streamlining effect on international law as a whole? This might be identified as a process of constitutionalisation. In this book, human rights can be understood as one of the core principles of international legal order and thus have an effect on the general law of treaties or on the settlement of disputes. Although human rights law is a relatively young field of international law, its content and core values today are of major importance for the interpretation of international law as a whole. As we witness a redefinition of sovereignty as a responsibility of states towards the people and a shift to greater relevance of the individual in international law in general, it is a logical consequence that human rights have an impact on other areas of international law.